Survey results on acceptance and use of Life Cycle Assessment among designers in world regions: IEA EBC Annex 72. Issue 3 (November 2020) - Balouktsi, M; Lützkendorf, T; Röck, M; Passer, A; Reisinger, T; Frischknecht, R
Abstract: Design practitioners' knowledge about Life Cycle Assessment (LCA) is crucial for the necessary decarbonisation of the built environment as well as the mitigation of other negative environmental impacts. Designers' attitudes towards LCA have so far been rarely analysed. In 2019, as part of the project IEA EBC Annex 72 "Assessing life cycle related environmental impacts caused by buildings", a global survey was conducted amongst design professionals within 23 countries. The aim was to investigate the level of awareness and acceptance of environmental performance assessment and LCA of buildings, the use of related information sources and tools as well as the application of Building Information Modelling (BIM) in connection to LCA. The results show that less than one third of designers currently provides or uses LCA services. The ones who do not are mainly constrained by the lack of client demand. To support an increased use of LCA during building design, not only it is necessary to provide related data and design/assessment tools, but also to establish standards/regulations to drive client demand. It is particularly relevant to include such requirements already in the client's brief. In future, an increased demand for building LCA results by institutional investors is expected.